2017
DOI: 10.3233/jad-160800
|View full text |Cite
|
Sign up to set email alerts
|

Amylin Enhances Amyloid-β Peptide Brain to Blood Efflux Across the Blood-Brain Barrier

Abstract: Findings from Alzheimer’s disease (AD) mouse models showed that amylin treatment improved AD pathology and enhanced amyloid-β (Aβ) brain to blood clearance; however, the mechanism was not investigated. Using the Tg2576 AD mouse model, a single intraperitoneal injection of amylin significantly increased Aβ serum levels, and the effect was abolished by AC253, an amylin receptor antagonist, suggesting that amylin effect could be mediated by its receptor. Subsequent mechanistic studies showed amylin enhanced Aβ tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…This effect was inhibited by amylin receptor antagonists and RAMP3 knockdown, further suggesting a role of AmR in mediating Aβ transport out of the brain across the BBB (Mohamed et al, 2017). Additionally, amylin treatments enhanced the Aβ brain-to-blood clearance likely by relocating low density lipoprotein receptor-related protein 1 (LRP1) from the cytosol to the membrane at the BBB.…”
Section: Elucidating the Mechanism Of Amylin Effects On Learning And mentioning
confidence: 99%
“…This effect was inhibited by amylin receptor antagonists and RAMP3 knockdown, further suggesting a role of AmR in mediating Aβ transport out of the brain across the BBB (Mohamed et al, 2017). Additionally, amylin treatments enhanced the Aβ brain-to-blood clearance likely by relocating low density lipoprotein receptor-related protein 1 (LRP1) from the cytosol to the membrane at the BBB.…”
Section: Elucidating the Mechanism Of Amylin Effects On Learning And mentioning
confidence: 99%
“…Amylin and Aβ have several common features such as having similar β-sheet structures 25 , binding to the same amylin receptor 26 , and being degraded by insulin degrading enzyme (IDE) 27 .Several studies have shown that amylin is involved in the pathogenesis of AD by inducing neuroinflammation and apoptosis 28 , but little is known about the mechanism by which amylin exacerbates AD pathology. On the other hand, multiple studies have shown that amylin ameliorated AD pathology by decreasing neuroinflammation and increasing Aβ clearance from brain to blood [29][30][31][32] . In this study, we investigated the effect of amylin and its alanog, pramlintide, on Aβ pathology, and identified a novel aspect of amylin and pramlintide in increasing the amyloidogenic processing of APP in TgSwDI mouse, a model for cerebral amyloid angiopathy (CAA) and AD, where both peptides increased γ-secretase complex level and APP localization in lipid rafts.…”
mentioning
confidence: 99%
“…High-speed AFM (HS-AFM) enabled the kinetic measurement of the structural dynamics of biological molecular processes [79][80][81][82][83][84] including amyloid aggregation [93,[108][109][110][111][112][113][114][115][116]. Here, we show that HS-AFM links structural and dynamics studies, reviewing recent HS-AFM studies and including our findings for Aβ42 [93] and amylin [116], which is associated with not only type II diabetes but also AD [117][118][119][120][121][122][123].…”
Section: Introductionmentioning
confidence: 64%
“…Amylin crosses the blood-brain barrier (BBB) [157][158][159], and its aggregate deposition is found in the brains of type II diabetes patients with AD [121]. The mechanisms underlying the pathological [122,123] and suppressive [117][118][119][120] effects of amylin to AD remain controversial [160].…”
Section: Aggregation Inhibition By Synthetic Polymersmentioning
confidence: 99%